A gold star for Zog - Donaldson, Julia; Scheffler, Axel (London ; New York : Arthur A. Levine Books, 2012)
Each year, as Zog practices new skills learned at Madam Dragon's school, a little girl helps him out until one day he finds a way to help make her dream come true for herself, a new friend, and Zog.
Publisher's Weekly
School Library Journal
Publisher's Weekly, May 2012
School Library Journal, June 2012
2.6
K-3
Keywords: Dragons -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Princesses -- Juvenile fiction; Schools -- Juvenile fiction; Dragons -- Fiction; Knights and knighthood -- Fiction; Princesses -- Fiction; Schools -- Fiction; Stories in rhyme; Dragons -- Fiction; Knights and knighthood -- Fiction; Princesses -- Fiction; School stories; Stories in rhyme; Picture books for children